Encyclopedia of African history and culture, Volume II : African Kingdoms (500-1500) - Page, Willie F., 1929-; Davis, R. Hunt. (New York NY : Facts On File, 2005)
A comprehensive encyclopedia on African history with a broad cultural and geographic sweep, this outstanding new set covers African history from ancient times to the present.
v. 1. Ancient Africa (Prehistory to 500 CE) -- v. 2. African Kingdoms (500 to 1500) -- v. 3. From conquest to colonization (1500 to 1850) -- v. 4. The Colonial Era (1850 to 1960) -- v. 5. Indepedent Africa (1960 to present).
"A Learning Source Book."
Includes bibliographical references and index.
Keywords: Africa -- Encyclopedias. -- African kingdoms -- 500 to 1500; Afrique -- Encyclopédies; Africa; Africa -- Enciclopedias; Encyclopedias; Encyclopedias